Body image in COPD and its relation with physical activity levels, lung function and body composition: An observational study - Freire, Ana Paula Coelho Figueira [UNESP]; Ferreira, Aline Duarte [UNESP]; Santos, Caroline Pereira [UNESP]; Araújo, Isabela Cristina Duarte [UNESP]; Uzeloto, Juliana Souza [UNESP]; Silva, Bruna Spolador de Alencar [UNESP]; Ramos, Dionei [UNESP]; Ramos, Ercy Mara Cipulo [UNESP] (Wiley, 2020)
Introduction: Body image has been previously defined as the mental figure we have of the contours and shape of our body; and the feelings concerning these characteristics. A change in body perception can influence one’s feelings of self-worth and compromise functional abilities. Thus, the detection of distortions in body image could be important data for clinical evaluation of subjects with COPD. Objectives: To assess the body image perception of subjects with COPD. Also, to investigate the association between body image and levels of physical activity in these subjects. Materials and Methods: 109 subjects were recruited and divided into the COPD group and control subjects without any pulmonary conditions. For this cross-sectional study, we performed an initial evaluation and participants were evaluated regarding physical activity level, body image (silhouette scale) and determination of body mass index (BMI). Finally, we performed the evaluation of lung function (spirometry) and body composition analysis (bioelectrical impedance). Results: BothCOPD and control subjects presented alterations in body image. Both groups desired significantly lower BMI and weight measures, according to the silhouette scale, demonstrating body dissatisfaction (P <.05). No differences in the level body dissatisfaction were found between Control and COPD groups (P >.05). No associations between physical activity levels and body image were observed (P >.05; r = −0.24 to 0.14). Conclusion: In conclusion, patients with COPD present significant body dissatisfaction, similar to control individuals. Furthermore, body image perception in COPD is related to body composition measurements but not to physical activity levels.
Keywords: body composition; body fat; body image; chronic obstructive; exercise; pulmonary disease